Effect of marital status on survival in glioblastoma multiforme by demographics, education, economic factors, and insurance status - Jun‐Chao Xie; Shuai Yang; Xue‐Yuan Liu; Yan‐Xin Zhao (Cancer Medicine)
Abstract The relationship between marital status and glioblastoma multiforme (GBM) has not been addressed in depth. Here, we aimed to investigate the association between marital status and survival in GBM. We searched the Surveillance, Epidemiology, and End Results (SEER) database and extracted the data of eligible patients diagnosed with GBM after 2004. Marital status was classified as married, divorced/separated, widowed, and single. A Kaplan‐Meier test was conducted to compare the survival curves of different groups. Multivariate Cox regression was performed to evaluate overall survival (OS) and cause‐specific survival (CSS) in different groups. Subgroup analysis was applied according to demographics, typical education and income levels in the locale, and insurance status. A total of 30 767 eligible patients were included. The median OS values were 9, 7, 3, 9 months in married, divorced/separated, widowed, and single patients, respectively. After adjustment for other covariates, married patients had better OS and CSS than other patients had. In addition to marital status, demographic factors, disease progression factors, local educational level, and insurance status were also associated with survival in GBM. Furthermore, subgroup analyses revealed the protective effect of marriage in most of the comparisons. Notably, the protective effect of marriage becomes more and more apparent as time goes on. The advantageous effect of marriage on GBM survival is especially prominent in patients who are male, older than 60 years of age, White, or living in middle‐income counties. In conclusion, marital status is an independent prognostic factor for GBM.